2006
DOI: 10.1126/science.1118079
|View full text |Cite
|
Sign up to set email alerts
|

Plasticization-Enhanced Hydrogen Purification Using Polymeric Membranes

Abstract: Polymer membranes are attractive for molecular-scale separations such as hydrogen purification because of inherently low energy requirements. However, membrane materials with outstanding hydrogen separation performance in feed streams containing high-pressure carbon dioxide and impurities such as hydrogen sulfide and water are not available. We report highly permeable, reverse-selective membrane materials for hydrogen purification, as exemplified by molecularly engineered, highly branched, cross-linked poly(et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
340
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 618 publications
(358 citation statements)
references
References 27 publications
12
340
1
Order By: Relevance
“…Moreover, the results revealed that the membranes retained their favorable properties even when additional compounds e.g. H 2 S and moisture were present [59]. Such findings are highly valuable since beside the main of the gas mixture constituents (H 2 , CO 2 , N 2 ) evolved during biohydrogen fermentation, certain trace compounds (e.g.…”
Section: 2mentioning
confidence: 90%
“…Moreover, the results revealed that the membranes retained their favorable properties even when additional compounds e.g. H 2 S and moisture were present [59]. Such findings are highly valuable since beside the main of the gas mixture constituents (H 2 , CO 2 , N 2 ) evolved during biohydrogen fermentation, certain trace compounds (e.g.…”
Section: 2mentioning
confidence: 90%
“…Ultraviolet light irradiation is a widely used technique for processing of polymer materials 8,[37][38][39][40] , for example, polymerization of novel gas-separation membranes 40 , creating nanostructures from block copolymer 8 , or surface modification of polymeric films (for example, polyimides and polydimethylsiloxane) 8,[37][38][39] . Enhancement of membrane-separation properties by ultraviolet surface modification is not uncommon.…”
mentioning
confidence: 99%
“…Hence PEG is considered an attractive material for separation of CO 2 from other gases. Moreover cross-linked PEGDa dense films do not show a pronounced selectivity loss due to plasticization, since the selectivity is based on solubility rather than on mobility [13].…”
Section: Introductionmentioning
confidence: 99%
“…Commercially important glassy polymeric membranes should be improved in terms of selectivity to compete with conventional processes, particularly in view of selectivity losses with mixed gases. Poly (ethylene glycol) (PEG) based polymers exhibit good CO 2 /N 2 selectivity (˛≥ 50), because of the higher solubility of CO 2 in polar PEG [12][13][14][15][16]. Hence PEG is considered an attractive material for separation of CO 2 from other gases.…”
Section: Introductionmentioning
confidence: 99%